Do anatomical defects after immediate repair of obstetric anal sphincter injuries correlate with urinary and bowel symptoms?. (7th June 2011) - Kanwar, S; Siddiqui, J; Phillips, K
Abstract : Aim: To correlate anatomical defects on endo-anal ultrasound with urinary and bowel symptoms. Methods: Prospective study over 12 months. 243 women sustained OASIS, 117 completed bowel symptoms questionnaire. Anal sphincter integrity was assessed both digitally and by endo-anal ultrasound. Symptomatic women were followed up with anal manometry. Results: There were 7470 deliveries in this time period. 5693 were vaginal deliveries, (including instrumental deliveries) of those there were 243 obstetric anal sphincter injuries. Among the obstetric anal sphincter injuries, there was a 23% episiotomy rate, 17% forceps rate and a 2% ventouse rate. Incidence of OASIS was 3.2% of all deliveries and 4.2% of vaginal deliveries. 6% of all women with OASIS had solid leakage, 15% liquid leakage and 45% had wind leakage. A sphincter defect was seen in 18% of women. Of which 15% had external sphincter defects alone, 0.8% had an internal sphincter defects alone and 2.5%had a defect in both the internal and external sphincter. Conclusion: Obstetric anal sphincter injury is non-significantly associated with bowel leakage. None of the women required an early second repair. The development of bowel symptoms does not seem related to sphincter defect on ultrasound. Instrumental delivery is not significant risk factor for OASIS. The endo-anal ultrasound revealed that the symptomatic women are not necessarily those with the defects.